Equilibrium and thermodynamics of Chromium (VI) adsorption on inert biomasses of Dioscorea rotundata and Elaeis guineensis - Villabona-Ortíz, Angel; Tejada-Tovar, Candelaria; González-Delgado, Angel Darío; Negrete-Palacio, Andrés; López-Genes, José (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Adsorption equilibrium on bioadsorbents was studied, and fitted to Langmuir, Freundlich and Dubinin-Radushkevich isothermal models, using yam peels (YP) and oil palm wastes (OPW) as bioadsorbents in the removal of hexavalent chromium present in aqueous solution, in a batch system, evaluating the effect of temperature, adsorbent dose and particle size on the process. Thermodynamic parameters were estimated by the Van't Hoff graphical method. It was found that the highest adsorption capacity was obtained at 0.03 g of adsorbent, 55 ºC and 0.5 mm of particle size. The equilibrium of adsorption on OPW is described by Langmuir and Freundlich isotherms, while that of YP by Dubinin-Radushkevich's model, indicating the adsorption is given by the ion exchange between the active centers and the metallic ion. The thermodynamic study determined that the elimination of YP is endothermic, irreversible, and not spontaneous and that for OPW it is exothermic, spontaneous at low temperatures, and irreversible.